Biological Approaches to Sustainable Soil Systems (CRC Press, 2009)
"For an ever-green revolution, we need, first and foremost, to have sustainable soil systems. … It is in this context that Biological Approaches to Sustainable Soil Systems is an extremely timely and valuable contribution to a wider understanding of what needs to be done for the sake of a truly modern agriculture and for the sake of future generations. …The book provides the scientific basis for low external-input agriculture. Soil health is treated in a holistic manner involving attention to the physics, chemistry, and microbiology of soil systems. The various chapters could help scientists chart out and embark on a program of "soil breeding" for high productivity. Such initiatives for sustainable agriculture should receive as much attention as crop breeding has been given if we are to promote advances in productivity in perpetuity without adverse ecological consequences." --From the foreword by M.S. Swaminathan, World Food Prize Laureate, Co-chair, UN's Millenium Task Force on Poverty and Hunger